Sustained Improvement of Appropriateness in Surgical Antimicrobial Prophylaxis with the Application of Quality Control Circle - Zou J; Zhong JY; Liu YX; Liu Y; Huang D; Xu BT; Li XW; Gong WJ; Tao J (Dove Medical Press, 2023)
Jian Zou,* Jia-Yun Zhong,* Yan-Xin Liu, Yu Liu, Dan Huang, Bian-Tiao Xu, Xi-Wen Li, Wen-Jun Gong, Jia Tao Department of Clinical Pharmacy, The People's Hospital of Pengzhou, Chengdu, People's Republic of China*These authors contributed equally to this workCorrespondence: Jian Zou, The People's Hospital of Pengzhou, No. 255 Second Section of South Third Ring Road, Chengdu, People's Republic of China, Tel +86 28 86239898, Email 70336641@qq.comPurpose: Quality control circle (QCC) has acquired success in many fields in healthcare industry as a process management tool, whereas its efficacy in surgical antimicrobial prophylaxis (SAP) remains unknown. This study aimed to implement QCC interventions to improve the appropriateness of SAP.Methods: A QCC activity team was established to grasp the current situation of SAP in clean surgery procedure, set target, formulate corresponding countermeasures and implement and review them in stages. The plan-do-check-act (PDCA) method was cyclically applied.Results: The appropriateness of antibiotic prophylaxis before (January to December 2020) and after (January to December 2021) the implementation of QCC activities were evaluated based on relevant international and Chinese SAP guidelines. The overall SAP appropriateness was significantly improved from 68.72% before QCC to 93.7% post QCC implementation (P< 0.01). A significant improvement (P< 0.05) was also determined for each category: selection (from 78.82% to 96.06%), duration (from 90.15% to 96.46%), indication (from 94.09% to 97.64%), timing of first dose (from 96.55% to 99.21%), antimicrobial usage (from 96.8% to 99.41%), re-dosing of antimicrobial (from 96.55% to 99.21%).Conclusion: Implementation of a QCC program can optimize the use of antibiotics and improve the appropriateness of SAP and is of practical importance to their standardization.Keywords: surgical antimicrobial prophylaxis, quality control circle, appropriateness